2017
DOI: 10.1057/s41261-017-0045-0
|View full text |Cite
|
Sign up to set email alerts
|

Bank governance and performance: a survey of the literature

Abstract: This research has been financed by the European Regional Development Fund through COMPETE 2020-Programa Operacional Competitividade e Internacionalização (POCI) and by Portuguese public funds through FCT (Fundação para a Ciência e a Tecnologia) in the framework of the project POCI-01-0145-FEDER-006890 Este trabalho foi financiado pelo Fundo Europeu de Desenvolvimento Regional (FEDER) através do COMPETE 2020-Programa Operacional Competitividade e Internacionalização (POCI) e por fundos nacionais através da FCT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 175 publications
(293 reference statements)
1
32
0
Order By: Relevance
“…Only by establishing a sound operation mechanism of the board can it be truly effective. This also suggest that as the size of the board of directors expands, the agency problem becomes more prominent and the coordination and communication between the board members become more difficult , then the negative effect of the communication would exceed its positive effect (Fernandes et al, 2018).…”
Section: Main Analysis and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only by establishing a sound operation mechanism of the board can it be truly effective. This also suggest that as the size of the board of directors expands, the agency problem becomes more prominent and the coordination and communication between the board members become more difficult , then the negative effect of the communication would exceed its positive effect (Fernandes et al, 2018).…”
Section: Main Analysis and Discussionmentioning
confidence: 99%
“…However, as the size of the board of directors expands, the agency problem becomes more and more prominent. When the number of board members exceeds the optimal range, the more time it takes for the coordination of the board members to ask, and the negative effect of the communication would exceed its positive effect (Fernandes et al, 2018). Mariappan and Thyagarajan (2018) found that board size was significantly related to performance when board size was between 6 and 9.…”
Section: Board Sizementioning
confidence: 99%
“…The literature supports using the following distinct measures of bank performance as summarized in Fernandes, Farinha, Martins, and Mateus's (2018) survey of literature: stock returns, Tobin's Q, ROE, ROA, accounting earnings, cost efficiency, profit efficiency, total interest plus noninterest expenses divided by assets, bank losses, non-performing assets, financial reactions based on CAMELS indicators, pre-tax operating income, net interest margin (NIM), return on average assets (ROAA), return on average equity (ROAE), loan losses, EBIT over total assets, likelihood to participate in bailout program, and amount of bailout funds. Additional research was conducted, and the literature supports the three most common measures of bank profitability: ROE, ROA, and NIM.…”
Section: Measuring Consequences On Profitability and Bank Performancementioning
confidence: 98%
“…They suggested that future research should consider additional variables such as board interlocks and directors' networks. Finally, Fernandes et al (2017a) concluded that lack of financial expertise on banks' boards could be a relevant factor in the 2007 financial crisis.…”
Section: Directors' Educational Level and Banks' Financial Performancementioning
confidence: 99%